Encephalitis is mediated by ROP18 of Toxoplasma gondii, a severe pathogen in AIDS patients - An, Ran (Proc Natl Acad Sci U S A, 2018)
The neurotropic parasite Toxoplasma gondii is a globally distributed parasitic protozoan among mammalian hosts, including humans. During the course of infection, the CNS is the most commonly damaged organ among invaded tissues. The polymorphic rhoptry protein 18 (ROP18) is a key serine (Ser)/threonine (Thr) kinase that phosphorylates host proteins to modulate acute virulence. However, the basis of neurotropism and the specific substrates through which ROP18 exerts neuropathogenesis remain unknown. Using mass spectrometry, we performed proteomic analysis of proteins that selectively bind to active ROP18 and identified RTN1-C, an endoplasmic reticulum (ER) protein that is preferentially expressed in the CNS. We demonstrated that ROP18 is associated with the N-terminal portion of RTN1-C and specifically phosphorylates RTN1-C at Ser7/134 and Thr4/8/118. ROP18 phosphorylation of RTN1-C triggers ER stress-mediated apoptosis in neural cells. Remarkably, ROP18 phosphorylation of RTN1-C enhances glucose-regulated protein 78 (GRP78) acetylation by attenuating the activity of histone deacetylase (HDAC), and this event is associated with an increase of neural apoptosis. These results clearly demonstrate that both RTN1-C and HDACs are involved in T. gondii ROP18-mediated pathogenesis of encephalitis during Toxoplasma infection.